The stolen generations : proceedings of the first national workshop, Alice Springs, September 1996 - National Stolen Generations Workshop 1996 : Alice Springs, N.T.); Gill, Rob.; North Australian Aboriginal Legal Aid Service. Stolen Generations Litigation Unit. (Darwin, N.T. : The Stolen Generations Litigation Unit of the North Australian Aboriginal Legal Aid Service, 1997)
Over 250 delegates from around Australia attended the first National Stolen Generations workshop; papers presented cover litigation possibilities, access to records at the Australian Archives, land rights legislation, reparation, personal stories.
Available from The Stolen Generations Litigation Unit of the North Australian Aboriginal Legal Aid Service, c/-Barbara Cummings, GPO 271, Darwin NT 0801.
Keywords: Stolen generations (Australia).; Children, Aboriginal Australian -- Congresses; Aboriginal Australians -- Removal -- Congresses; Aboriginal Australians -- Child welfare -- Congresses; Aboriginal Australians -- Government policy -- Congresses; Law - Land; Law - Legal system; Child welfare - Child / parent separation - Stolen generations; Australia